Peran Faktor Non Ekonomis dalam Penyelenggaraan Pendidikan - Iskandar Agung; Gatot Subroto (Jurnal Pendidikan dan Kebudayaan, 2010)
The objectives of this study is to identify direct effect, indirect effect, and totally effect of variables of organizational culture, leadership, and job satisfaction to teachers performance. The study was conducted in several Public Senior High Schools categorized as outstanding schools in Jakarta in 2009. Outstanding schools are schools which have already achieved the â€œplusâ€ school criteria by the Jakarta Province Education Office. From the 41 selected schools categorized as outstanding schools in Jakarta, ten of them was selected as sample schools. The samples of the respondents are 150 teachers who are selected using proportional random sampling technique. Data was collected by using questionnaire. Before the questionnaire was distributed, the study performs some initial testing in order to make sure its validity and reliability using Product Moment Correlation test and Alpha Cronbach test. To do the hypothetical testing, the researcher firstly tests the data being obtained with normality, homogeunity, and linearity testing, included model testing. The finding of this study shows that: 1) organizational culture and leadership has a significant influences to job satisfaction of the teachers; 2) organizational culture, leadership, and job satisfaction also have a significant influences to teachersâ€™ performance.Â ABSTRAKÂ Tujuan studi ini untuk mengidentifikasi pengaruh langsung, tidak langsung, dan total dari variabel budaya organisasi, kepemimpinan, dan kepuasan kerja terhadap kinerja pendidik/guru. Studi dilaksanakan di 10 SMA Negeri kategori unggulan (plus kotamadya, provinsi, dan berstandar nasional/internasional) di provinsi DKI Jakarta. Sampel responden dalam studi berjumlah 150 orang yang diambil melalui teknik proporsional random sampling. Data diperoleh melalui penyebaran kuesioner. Sebelum kuesioner disebarkan kepada responden, dilakukan pengujian validitas dan reliabil itas dengan menggunakan tes product moment correlation dan alpa cronbach. Untuk pengujian hipotesis, dilakukan pengujian persyaratan analisis terhadap data untuk mengetahui normalitas, homogenitas, dan linearitas data, termasuk pengujian fit model. Hasil studi menunjukkan bahwa: 1) budaya organisasi dan kepemimpinan di sekolah memiliki pengaruh positif terhadap kepuasan kerja; 2) budaya organisasi, kepemimpinan, dan kepuasan kerja memiliki pengaruh positif terhadap kinerja guru di sekolah.Â